THE STATE OF GENERATIVE FUNCTION IN WOMEN INFERTILE WOMEN - Gulsanam B. Malikova; Bakhtiyor M. Abdurahmonov (Central Asian Journal of Medicine, 2023)
A wide range of STIs can contribute to a high incidence of inflammatory disease and, as a consequence, intracanalicular obstruction with the onset of sexual activity.